Laparoscopic correction of intestinal malrotation in adult - Nilanjan Panda; Nitin Kumar Bansal; Mohan Narasimhan; Ramesh Ardhanari (Journal of Minimal Access Surgery, 2014)
Intestinal malrotation is rare in adults. Patients may present with acute obstruction or chronic abdominal pain. These symptoms are caused by Ladd′s bands and narrow mesentery resulting from incomplete gut rotation. Barium, computed tomography (CT) and magnetic resonance imaging (MRI), angiography and sometimes explorative laparotomy are used for diagnosis. Ladd′s procedure is the treatment of choice but data about laparoscopic approach in adult is scarce. We report three cases of laparoscopic correction of adult malrotation presenting with chronic abdominal pain. The diagnosis is made by CT/MRI. Laparoscopic Ladd′s procedure (release of bands, broadening of mesentery and appendicectomy) was performed via three ports. Procedure time 25-45 min. All patients were discharged on postoperative day 2. At 6 month follow-up, all are symptom free. Laparoscopic Ladd′s procedure is an acceptable alternative to the open technique in treating chronic symptoms of intestinal malrotation in adults.